(untitled) (Research, Society and Development, 2022)
Thyroid function is closely associated with neuropsychological functions, including mental status and cognitive functions. Subclinical hypothyroidism (HSC) is defined as a condition with elevated levels of thyroid stimulating hormone (TSH) and normal levels of free thyroxine (T4). Although the role played by thyroid hormones in the pathophysiology of mental disorders is unclear, it has been suggested that small changes in thyroid hormone levels, even within the normal range, may be related to altered brain function in depression. Currently, there are 2 explanatory hypotheses: serotonin deficit and noradrenaline deficit in the central nervous system caused by hormonal disorders. It is important to emphasize that the thyroid-psychic pathway is bidirectional, therefore, both thyroid alterations can cause depressive symptoms or exacerbate a previous psychiatric pathology, and depression can promote thyroid disorders, the latter being less frequent. Thus, the role of thyroid function in depressive illness is unclear. Although there is some evidence that mild thyroid alterations predispose to cases of depression, the specific abnormalities involving the thyroid and depressive conditions remain poorly understood. However, there is a causal link.